Two case reports of intravenous Midazolam sedation in patients with down syndrome receiving dental treatment - Mohd, Farah Natashah; Said, Abdul Hadi; Ismail, Mohd Nizamuddin (Ectodermal Dysplasia Group-Turkey, 2022)
Abstract